Welwitschianalol A and B, two cyclohexene derivatives and other insecticidal constituents of Caesalpinia welwitschiana (Oliv.) Brenan. (December 2017) - Essoung, Flaure Rosette Ehawa; Mba'ning, Brice Mittérant; Mohamed, Samira Abuelgasim; Lwande, Wilber; Ngouela, Silvère Augustin; Tsamo, Etienne; Chhabra, Sumesh Chander; Hassanali, Ahmed; Cox, Russell John
Graphical abstract: Welwitschianalol A (1) and B (2) isolated from Caesalpinia welwitschiana (Fabaceae) showed good insecticidal activity on Tuta absoluta larvae with LD50 of 4.11 and 3.81 ppm respectively. Highlights: New compounds welwitschianalol A and B isolated from Caesalpinia welwitschiana . All compounds were elucidated based on spectroscopic methods. Each compound showed good larvicidal activity (LD50  < 6.8 ppm) against Tuta absoluta . Welwitschianalol B was the most potent compared to others and azadirachtin. Abstract: Crude methanol extract of the leaves of Caesalpinia welwitschiana was found to possess moderate larvicidal activity against second-instar larvae of Tuta absoluta Meyrick. Bioassay-guided fractionation of this extract led to the isolation of two oxygenated cyclohexene derivatives, welwitschianalol A (1, (1 α, 2 β )-2-acetoxy-1-hydroxy-1- benzoyloxymethylcyclohex-5-ene) and B (2, (1 α, 2 β )-2- benzoyloxy −1-cinnamoyloxymethyl-1-hydroxycyclohex-5-ene), together with eight known compounds, comprising bonducellin, dipteryxic acid, 3′-hydroxygenkwarin, afzelin, quercitrin, myricitrin, methyl gallate and gallic acid. The structures of the unknown compounds as well as those of the known ones were elucidated based on their MS, 1D and 2D NMR spectra, and in the case of known compounds, by comparison with the reported data. Each of welwitschianalol A and B, bonducellin, dipteryxic acid, afzelin, quercitrin and myricitrin showed more than 50% mortality of T. absoluta larvae at 5 ppm, which was comparable to that of azadirachtin (the most bioactive constituent of Azadirachta indica ). The most potent constituent of C. welwitschiana was welwitschianalol B with LD50 of 3.8 ppm, which was higher than that of azadirachtin (LD50 of 7.8 ppm).